Bioelectrical impedance: effect of 3 identical meals on diurnal impedance variation and calculation of body composition - Slinde, Frode; Rossander-Hulthén, Lena (The American journal of clinical nutrition, 2001)
Bioelectrical impedance analysis (BIA) can be used for estimating body composition. Earlier studies showed that the ingestion of meals lowers bioelectrical impedance, but none studied the effect of repeated ingestion of an identical meal in narrow intervals on impedance measurements during 24 h. The objectives were to study the effect on bioelectrical impedance of 3 identical meals and to compare the results from single-frequency BIA measurements with those from multiple-frequency BIA measurements. Bioelectrical impedance was measured 18 times during 24 h in 18 healthy subjects [10 women and 8 men; x +/- SD age: 31.5 +/- 11.7 y; body mass index (in kg/m(2)): 22.2 +/- 2.7]. An identical meal was given at breakfast, lunch, and dinner. Bioelectrical impedance decreased after ingestion of a standard meal (P < 0.05). The decrease in impedance lasted 2-4 h after each meal. The decrease was additive during the day, although it was more pronounced after the first meal because of the combined effect of rising from the supine position and meal ingestion. This is an important consideration when calculating body composition: percentage of body fat varied by 8.8% from the highest to the lowest measurement in women and by 9.9% from the highest to the lowest measurement in men. The bioelectrical impedance at 50 kHz was identical when measured with multiple frequencies or a single frequency. The ingestion of meals leads to an additive decrease in bioelectrical impedance and thus to a decrease in the calculated percentage of body fat.